2011
DOI: 10.1128/jvi.05095-11
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the Components of the HIV Life Cycle in Productively Infected CD4 + T Cells in a Population of HIV-Infected Individuals

Abstract: We estimate the time required for HIV to complete separate stages of its infection cycle in productively infected CD4؉ T cells in vivo by comparing initial delays after administration of single antiretroviral drugs until HIV RNA reduction in peripheral blood. Data were obtained from monotherapy studies of eight antiretroviral drugs from all currently licensed HIV drug classes: CCR5 blockers (maraviroc), fusion inhibitors (enfuvirtide), nucleoside and nonnucleoside reverse transcriptase inhibitors (abacavir, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 41 publications
4
87
0
Order By: Relevance
“…Interestingly, we recently showed 2 that a biphasic viral decline was also observed in patients treated with lonafarnib, a prenylation inhibitor, which was previously shown to block HDV assembly/secretion. 3 The similarity in the pattern of viral decline reinforces our conclusion that an additional effect in blocking viral infection cannot be ruled out, but that the main mechanism of action of IFN is blocking viral production.…”
Section: Replysupporting
confidence: 62%
See 1 more Smart Citation
“…Interestingly, we recently showed 2 that a biphasic viral decline was also observed in patients treated with lonafarnib, a prenylation inhibitor, which was previously shown to block HDV assembly/secretion. 3 The similarity in the pattern of viral decline reinforces our conclusion that an additional effect in blocking viral infection cannot be ruled out, but that the main mechanism of action of IFN is blocking viral production.…”
Section: Replysupporting
confidence: 62%
“…In contrast, inhibition of new infection will take a while to manifest itself on virion levels in serum given that a cell infected just before therapy will take some time to produce virus as the infection progresses through its complete replication cycle within that cell. This difference of effect determined by the length of the initial delay before viremia decreases has been observed in human immunodeficiency virus (HIV) by Murray et al 3 Monotherapy that inhibits fusion of a virion with a cell showed a larger initial delay in response than a drug that inhibited a later stage, such as integration of HIV DNA into the cell genome. All of these results and the long delay before HDV RNA decreases after IFN suggest that this drug impacts on new infection, rather than the much later stage of HDV virion production.…”
Section: Effect Of Interferon-alpha Therapy On Hepatitis D Virusmentioning
confidence: 99%
“…This model is a simple extension of the basic model of viral infection [1] and similar models have been proposed [12, 23, 26]. Here, as has been done before [1, 6], we assume that the plasma HIV RNA is at set-point before therapy, that the virus and infected cells are in quasi-steady state (i.e., V ≈ p I 2 / c ), and, as we focus on the early viral kinetics, we make the standard approximation that the number of target cells remains constant.…”
Section: Methodsmentioning
confidence: 99%
“…Active targeting exploits these viral components on the cell surface to selectively identify the infected cells from the uninfected ones [13]. Active replication of HIV in vivo, from the point of infection of a CD4 T-cell to release of viral progeny takes an average of 52 hours for completion [14]. This long generation time of HIV could be effectively utilized to specifically deliver the anti-retroviral drugs to the infected cells by nanotechnology methods.…”
Section: Targeted Drug Delivery To Infected Cellsmentioning
confidence: 99%